Hunting trophy import bans proposed by the UK may be ineffective and inequitable as conservation policies in multiple social‐ecological contexts - Douglas A. Clark; Peadar Brehony; Amy Dickman; Lee Foote; Adam G. Hart; Charles Jonga; Moreangels M. Mbiza; Dilys Roe; Chris Sandbrook (Conservation Letters, 2023)
Abstract The UK government is considering legislation to prohibit the importation of hunting trophies. We examine documented social, ecological, and political outcomes of two previous such bans. We find that the UK government's proposal shares the shortcomings of existing bans that have (1) failed to address, or have even amplified, key threats to hunted species, (2) imposed costs on citizens of other countries, and (3) delegitimized the Convention on International Trade in Endangered Species (CITES). Trophy import bans are blunt policy instruments that can cause more problems than they solve.